Low Incidence of Postoperative Respiratory Depression with Oliceridine Compared to Morphine: A Retrospective Chart Analysis - Sergio Bergese; Richard Berkowitz; Paul Rider; Martin Ladouceur; Suzanne Griffith; Alvaro Segura Vasi; Kristina Cochrane; Linda Wase; Mark A. Demitrack; Ashraf S. Habib (Pain Research and Management)
Background. Oliceridine, an investigational IV opioid, is a first-in-class G-protein selective agonist at the μ-opioid receptor. The G-protein selectivity results in potent analgesia with less recruitment of β-arrestin, a signaling pathway associated with opioid-related adverse events (ORAEs). In randomized controlled studies in both hard and soft tissue models yielding surgical pain, oliceridine provided effective analgesia with a potential for an improved safety and tolerability profile at equianalgesic doses to morphine. The phase 3, open-label, single-arm, multicenter ATHENA trial demonstrated the safety, tolerability, and effectiveness of oliceridine in moderate to severe acute pain in a broad range of patients undergoing surgery or with painful medical conditions warranting use of an IV opioid. This retrospective, observational chart review study compared respiratory depression events associated with oliceridine administration as found in the ATHENA trial to a control cohort treated with conventional opioids. Methods. Patients at 18 years of age or older, who underwent colorectal, orthopedic, cardiothoracic, bariatric, or general surgeries between June 2015 and May 2017 in 11 sites participating in the ATHENA trial who received postoperative analgesia either with IV oliceridine or with IV conventional opioids (e.g., morphine alone or in combination with other opioids) (CO cohort); and had a hospital stay >48 hours, were included in this retrospective analysis. Data from the ATHENA trial was used for the oliceridine cohort; and additional baseline characteristics were collected from medical charts. Data from medical charts were collected for all CO cohort patients. The two cohorts were balanced using an inverse probability weighting method. The primary outcome was the incidence of operationally defined opioid-induced respiratory depression (OIRD) in the two cohorts. Secondary outcomes included between-group comparison of the incidence of OIRD events among a subset of high-risk patients. Results. OIRD was significantly less in the oliceridine cohort compared to the CO cohort (8.0% vs. 30.7%; odds ratio: 0.139) (95% confidence interval [CI] 0.09–0.22; P<0.0001). Likewise, the incidence of OIRD was lower among high-risk patients in the oliceridine cohort (9.1% vs. 34.7%; odds ratio: 0.136) (95% CI [0.09–0.22]; P<0.0001) compared to the CO cohort. Conclusion. In this retrospective chart review study, patients receiving IV oliceridine for moderate to severe acute pain demonstrated a lower incidence of treatment emergent OIRD compared to patients who were treated with IV morphine either alone or with concomitant administration of other opioids.